2017
DOI: 10.1097/icu.0000000000000418
|View full text |Cite
|
Sign up to set email alerts
|

The use of optical coherence tomography in neuro-ophthalmology

Abstract: It is crucial for neuro-ophthalmologists to be updated and familiar with these newer OCT imaging protocols and to make appropriate choices for different clinical scenarios, in order to optimize the diagnostic sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 64 publications
1
24
0
Order By: Relevance
“…[3][4][5][6][7][8] Previous studies have shown that neither the use of systemic steroid nor interferon-beta altered the degree of RNFL thinning up to 4 months after optic neuritis. 9,10 The aim of this study was to assess the longitudinal changes in RNFL thickness after a first attack of optic neuritis and to investigate the impact of treatment on RNFL thinning at 1 year after the attack.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Previous studies have shown that neither the use of systemic steroid nor interferon-beta altered the degree of RNFL thinning up to 4 months after optic neuritis. 9,10 The aim of this study was to assess the longitudinal changes in RNFL thickness after a first attack of optic neuritis and to investigate the impact of treatment on RNFL thinning at 1 year after the attack.…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed Humphrey Visual Field (HVF) data by mean deviation (dB) of the nasal and temporal hemifield using the Hood-Kardon linear model [22, 23]. The contralateral temporal field and ipsilateral nasal field were averaged as “abnormal” and the contralateral nasal field and ipsilateral temporal field were averaged as “control”.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike the GCC, which demonstrates clear segregation of the crossed and the non-crossed visual pathways into the nasal and temporal retinae, respectively, all 4 quadrants of the RNFL contain a combination of crossed and non-crossed fibers. However, the nasal quadrant is known to contain preferentially more crossed fibers, while the superior, inferior, and temporal quadrants contain a majority of non-crossed fibers [23, 35]. Therefore, we analyzed crossed fibers using nasal quadrants, with nasal retina contralateral to the brain lesion as “abnormal” and ipsilateral nasal retina as “control.” We then analyzed non-crossed fibers as an average of superior and inferior quadrants of RNFL; superior and inferior retina ipsilateral to the brain lesion were defined as “abnormal” and contralateral superior and inferior retina as “control”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The instrument uses speci¯c algorithms to automatically measure retinal thickness (RT) and retinal nerve¯ber layer (RNFL), to quantify optic nerve head (ONH) morphology and to assess changes in retinal diseases. 1 This is especially important in children because visual loss associated with retinal disease can negatively in-°u ence their visual development. 2 Wang et al 3 revealed that magni¯cation attributable to axial length (AL) and refractive error has minimal impact on measurements of macular and RNFL thickness in 120 children, but they asserted that transverse measurements such as optic disc diameter should be corrected by magni¯cation effect.…”
Section: Introductionmentioning
confidence: 99%